Leader–subordinate congruence in power distance values and voice behaviour: A person–supervisor fit approach. Issue 1 (9th May 2021) - Guzman, Felipe A.; Fu, Xin
Abstract: Although the literature on voice suggests that subordinates low in power distance values (i.e. those who neither believe nor accept the unequal distribution of power in organisations) should engage in voice behaviour more frequently, the empirical research has returned equivocal findings. Drawing from person–supervisor (P–S) research, we propose that subordinates' decision to engage in voice depends on the joint effects of leaders and subordinates' power distance values. Specifically, we investigate varying configuration of leader–subordinate power distance congruence and incongruence on subordinates' voice. Additionally, as employees' values may constitute more distal antecedents of voice behaviour, we also examine the mediating role of affective trust in the leader as affective trust constitutes a more proximal antecedent of proactive behaviours such as voice. Utilising data from 236 subordinates and their leaders, our results show that voice is most frequent when (a) leaders and followers share low power distance values and (b) when leaders score low and subordinates high on these values. Additionally, affective trust fully mediates the relationship between power distance value congruence and voice. We discuss the theoretical and practical implications of our findings.